Implementasi Elemen Olahraga pada Struktur dan Bentuk Bangunan dalam Perancangan Gelanggang Olahraga Indoor - Yuwono, Natanael Dirgantara Putra; Soemarwanto, Dadoes; Faisal, Muhammad (Rifa'Institute, 2023)
Sports activities have become the most popular activities among people after Covid-19. The place that is often used by people to exercise is the sportshall. When designing a sportshall, it is necessary to add sports elements to the sportshall so that the public can understand its function just by making visual contact. In designing this sportshall, futsal and basketball were used as examples of the application of elements in this sportshall. The sports element taken is the ball, because the ball is an important element in futsal and basketball. As an implementation, the shape and structure of this sportshall was chosen. The structure uses a